Zagreb Stock Exchange Trends in 2017 - Domagoj Cingula; Sime Vucetic; Ivana Gazic (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
Global financial crisis of 2008 had strong influence on world markets, where emerging and less developed ones were affected the most, their recovery lasted longer, and it still lasts. Zagreb Stock Exchange (ZSE) main index, CROBEX, reached its all-time high value (ATH) on January 4, 2008 with 5.292,14 points , while all-time low was reached on March 9, 2009 (1.239,17 points). Years later, CROBEX is still performing much closer to its lowest values, with the best result of 2.006,24 points in 2016 (highest value on 10.10.2016.). Just a few days of 2017 were enough for CROBEX to break the psychological 2.000 points barrier, yet economic environment in Croatia has suddenly become destabilized and it stopped one more local stock exchange recovery attempt in March. One of the biggest regional food and beverages producers, distributor and retail chain was put under procedure of compulsory administration, based on the "Law on Extraordinary Administration Procedure in Enterprises of Systematic Importance for the Republic of Croatia" («Lex Agrokor»), which affected stock prices of companies that are part of this concern, but also their suppliers and market in general. Since then, CROBEX has been moving around 1800-1900 points, and its liquidity has deteriorated. As stock market trends represent a useful tool, or better to say an indicator of the financial system and economic development level, this paper analyses recent movements on ZSE.
Keywords: 650; CROBEX; Economic Development; Financial Market; Index; Zagreb Stock Exchange